2020
DOI: 10.1021/acs.joc.9b03020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nβ-Substituted α,β-Diamino Acids via Stereoselective N-Michael Additions to a Chiral Bicyclic Dehydroalanine

Abstract: The highly diastereoselective 1,4-conjugate additions of several nitrogen nucleophiles to chiral bicyclic dehydroalanines have been assessed effectively at room temperature in good to excellent yields without needing any catalyst or additional base. This methodology is general, simple, oxygen and moisture tolerant, high-yielding, totally chemo-and stereoselective. Significantly, most of the reaction adducts were obtained in nearly quantitative yield without column chromatography purification. This procedure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 76 publications
(182 reference statements)
0
9
0
Order By: Relevance
“…157 Successful stereoselective syntheses of this crosslink have been reported by several groups. 158,159 Arginine. Recently, Eyre et al reported a new crosslink in cartilage formed by the spontaneous oxidation of a ketoamine with arginine to produce arginoline 57 (Fig.…”
Section: Other Amino Acid Containing Divalent Crosslinksmentioning
confidence: 99%
“…157 Successful stereoselective syntheses of this crosslink have been reported by several groups. 158,159 Arginine. Recently, Eyre et al reported a new crosslink in cartilage formed by the spontaneous oxidation of a ketoamine with arginine to produce arginoline 57 (Fig.…”
Section: Other Amino Acid Containing Divalent Crosslinksmentioning
confidence: 99%
“…Besides carrying out asymmetric reductions of α,β-diamino alkenes as shown in Scheme 40, another synthetically usefully alkene-based strategy towards α,β-diamino acids are aza-Michael-initiated approaches (Scheme 41 and Scheme 42). [91][92][93][94] Several complementary, either catalyst-or chiral auxiliarycontrolled asymmetric protocols have been reported to achieve this transformation. One of the most commonly employed strategies is to carry out the addition of suited N-nucleophiles to chiral Ni complexes 180, as demonstrated by numerous research groups over the last years (Scheme 41A).…”
Section: α-Nr 2 -β-Aa Derivatives Starting From Alkenesmentioning
confidence: 99%
“…The Michael addition reaction is one of the most powerful and valuable tools for the formation of C-X (X = C, O, N, S) bonds, which plays a vital role in organic synthetic chemistry. [1][2][3] It is one of the most typical reactions between a nucleophile called a Michael donor and an activated Michael acceptor, and a huge number of optically functional structures and natural products have been prepared by this important transformation over the years. Meanwhile, the nucleophilicity and reactivity of alcoholic hydroxyl are relatively poor, but the oxa-Michael reaction, as an important part of the Michael reaction for the construction of the C-O bond, has also received considerably…”
Section: Introductionmentioning
confidence: 99%